PERSAINGAN PASAR OLIGOPOLI DI INDONESIA - Layalia Hilwa; Ulli Ngutfah; Ngizatul Laela; Muhammad Ikbar Rais; Naerul Edwin Kiky Aprianto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The oligopoly market is a complex business environment where only a few companies dominate the market. In this context, competitive strategy plays an important role in determining the success of the company and the balance of the market. Each company decides its own policy and all the company's actions as price changes will be taken into account by other companies, because every company in the market believes in the wisdom of a company. An oligopoly agreement is a form of agreement where business actors who own all kinds of objects or an activity. This study aims to determine the competitiveness of Telecommunication Companies (Indosat, XL Axiata, Smartfren,) in the oligopoly market in Indonesia. In its competition, telecommunication companies have carried out Maximum Structure Conduct Performance. The method used in this study is literature or research by examining various references in the form of books, magazines, and notes.